An analysis of longevity risk in a portfolio of life annuitants - Njeri, Sharon (Strathmore University, 2015)
Longevity risk has economic significance for governments, individuals and corporations. There is need to analyze the expected future lifetime of a population anticipating to receive lifetime benefits in Kenya. This paper performs such an analysis on the annuitants of a Kenyan life insurance company by making use of the Lee carter model and further describes ways to manage this risk. The results of this paper are directly relevant to annuity providers. It is found that life expectancy is increasing in the future up to some point where it gradually decreases. Conclusions made are that several models should be used to investigate this risk so as to reduce model errors and that impact of the data used is financially material.. Suggestions are that companies should create Value at Risk estimates of capital to cover this risk over one year periods and that more research should be done on managing longevity risks by use of capital markets in the country.